Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Kementerian Perdagangan Republik Indonesia - Riana Agustin; Murti Wijayanti (Departement of Mathematics Education, 2023)
This study aims to examine the influence of the work environment, work discipline and work motivation on employee performance at the Ministry of Trade of the Republic of Indonesia. The method used is quantitative with sampling using probability sampling technique. The total population in this study was 2,909 employees with 207 respondents selected at random (random sampling). Primary data for this study were collected by distributing questionnaires to employees at the Ministry of Trade of the Republic of Indonesia. The software used is Smart PLS 3.0. The results of this study reveal that: 1) Work Environment has a significant effect on Employee Performance with a standard value at the P-value level <0.05 (0.043 <0.05); 2) Work Discipline has a significant effect on Employee Performance with a standard value at the P-value level <0.05 (0.011 <0.05); 3) Work Motivation has a significant effect on Employee Performance with a standard value at the P-value level <0.05 (0.000 <0.05); 4) Work Environment, Work Discipline and Work Motivation together have a significant effect on Employee Performance with an F-count of 288.47 > F-table of 2.65 and the value of the coefficient of determination (R2) in R-Square obtains a value of 81 percent.